Effect of Transcodent painless needles on injection pain in maxillary anterior infiltration: a split‐mouth controlled randomized clinical trial - Farnoosh Razmara; Arjang Baghi; Farzaneh Afkhami (Wiley, 2022)
Abstract Objectives The present study aimed to determine the pain perceived during supraperiosteal (infiltration) injection in anterior maxillary region by Transcodent painless needle tips in comparison to the regular needle tips. Material and methods In this split‐mouth controlled randomised clinical trial, 30 patients were selected as candidates for cosmetic treatment who needed infiltration injections on both sides of canine area. They were each administered 0.9 mL of Lidocaine HCl 2% with epinephrine 1:100,000 in the buccal vestibules using two types of needle tips, Transcodent painless needle tip or regular needle tip. Immediately after the injection, the pain was measured using a 100 mm visual analog scale. The level of pain was statistically analyzed in the two groups using the parametric paired t‐test. A 5% significance level was considered for statically significant difference between two means. Results In accordance with the results, the patients' level of pain were estimated as 18.3 ± 10.7 mm with Transcodent painless needle tips and 43.1 ± 13.1 mm in regular needle tip (p < 0.05). Conclusion The Transcodent painless needle showed considerable reduction of pain in the anterior maxillary infiltration when compared to the regular needle tips.